DaBlaCa-13 Study: Oncological Outcome of Short-Term, Intensive Chemoresection With Mitomycin in Nonmuscle Invasive Bladder Cancer: Primary Outcome of a Randomized Controlled Trial. Issue 2 (12th October 2022) - Lindgren, Maria S.; Hansen, Erik; Azawi, Nessn; Nielsen, Anna M.; Dyrskjøt, Lars; Jensen, Jørgen B.
Abstract : PURPOSE: This study aimed to assess long-term follow-up after chemoresection with mitomycin (MMC), a nonsurgical treatment modality for recurrent nonmuscle invasive bladder cancer (NMIBC). At the time of recurrence, chemoresection has previously been shown to reduce the number of patients requiring a procedure (transurethral resection of bladder tumors [TURBT] or office biopsy) by more than 50%. This study investigated the number of patients requiring a procedure during initial treatment and 2-year follow-up in patients treated with short-term, intensive chemoresection with MMC compared with patients undergoing standard surgical treatment of recurrent NMIBC. METHODS: A randomized, controlled trial was conducted in two urological departments in Denmark from January 2018 to August 2021. In total, 120 patients with a history of Ta low- or high-grade NMIBC were included upon recurrence. The intervention group received intravesical MMC (40 mg/40 mL) three times a week for 2 weeks and TURBT or office biopsy only if the response was incomplete. The control group received TURBT or office biopsy and 6 weekly adjuvant instillations. The primary outcome was the number of patients undergoing a procedure within 2 years from inclusion, which was compared between groups using the chi-squared test. Recurrence-free survival was analyzed using the Kaplan-Meier method. RESULTS: Significantly fewer patients were in need of a procedure in the intervention group than in the control group: 71% (95% CI, 57 to 81) and 100% (95% CI, 94 to 100), P < .001. The 12-month recurrence-free survival was 36% (95% CI, 24 to 50) and 43% (95% CI, 30 to 56) in the intervention and control groups, respectively ( P = .5). CONCLUSION: Short-term intensive chemoresection is an effective treatment strategy for recurrent NMIBC that leads to a reduced number of required procedures without compromising long-term oncological safety.